MACROECONOMIC DETERMINANTS AND EQUITY MARKET DYNAMICS: A JOHANSEN CO-INTEGRATION AND GRANGER CAUSALITY ANALYSIS OF THE BSE SENSEX - S. Kavitha; Joghee, Mehta Vani; S. Padmanaban (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Stock markets play a vital role in channelling capital and driving economic growth. They act as platforms where investors trade assets at established prices. A variety of factors influence the returns investors expect, with macroeconomic indicators being among the most critical. Changes in these indicators can have a substantial impact on stock price movements. For both investors and policymakers, macroeconomic variables are key signals that reflect the overall economic environment. Stock market trends also provide valuable insights into investor sentiment and expectations regarding the economy's future trajectory. By offering a comprehensive view of economic health and stability, macroeconomic factors shape investment strategies and guide policy decisions. The study aims to examine the impact of select macroeconomic variables on the performance of the BSE Sensex. It analyses monthly data from June 2022 to March 2024, including variables such as the BSE Sensex, GDP, gold prices, inflation rate, unemployment rate, and exchange rate. To identify any issues related to stationarity, the ADF test was applied. The Johansen co-integration method was then used to explore long-term relationships between the dependent and independent variables. Additionally, the Granger causality test was conducted to determine the direction and nature of causal relationships among the variables.